PENGARUH MODEL CTL BERBANTUAN METODE PROBLEM SOLVING TERHADAP HASIL BELAJAR MATEMATIKA DI SD NO. 2 DALUNG - Permata Sari, Ni Made Indah; Ni Gusti Ayu Made Yeni Lestari; I Made Putra Aryana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effect of the Contextual Teaching and Learning learning model assisted by the Problem Solving method on students' mathematics learning outcomes. The subjects of this study were fifth-grade students of SD No. 2 Dalung, North Kuta, consisting of an experimental class and a control class with 28 students each. Data collection methods were tests, observations, and interviews. The collected data were analyzed using descriptive analysis, prerequisite tests, and hypothesis testing using an independent sample t- test. The results of the study showed that (1) the mathematics learning outcomes of students in the control class increased from an average pretest of 60.86 to 72.39 in the posttest, (2) the mathematics learning outcomes of students in the experimental class increased from an average pretest of 61.71 to 85.29 in the posttest, and (3) there was a significant influence of the application of the Contextual Teaching and Learning learning model assisted by the Problem Solving method on the mathematics learning outcomes of fifth grade students of SD No. 2 Dalung, North Kuta, as evidenced by a significance value of 0.000 <0.05, so that H0 was rejected and H1 was accepted.